Layer-by-layer assembly of a polymer of intrinsic microporosity: targeting the CO2/N2 separation problem. Issue 30 (26th March 2019) - Pramanik, Nabendu B.; Regen, Steven L.
Abstract : A polymer of intrinsic microporosity has been successfully incorporated into 6 nm thick polyelectrolyte multilayers and found to exhibit exceptional permeability properties with respect to CO2 and N2 . Abstract : A polymer of intrinsic microporosity, 1, has been incorporated into a series of polyelectrolyte multilayers via the layer-by-layer deposition method. One of these assemblies [a 6 nm multilayer derived from1 plus poly(diallyldimethylammonium chloride)] showed exceptional permeation properties with respect to CO2 and N2 . Specifically, this film exhibited a CO2 permeance of 130 GPU and a CO2 /N2 selectivity of 33.